Penguatan Soft Skills Manajerial melalui Pelatihan Leadership, Teamwork, dan Problem Solving - Rozalina Novianty; Sutawa Sutawa; Misnan Misnan (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
Developing soft skills is crucial for preparing the younger generation to face the challenges of higher education and the 21st-century workforce. However, some high school students still lack proficiency in leadership, teamwork, and problem-solving—competencies that constitute managerial soft skills. This community service initiative aimed to enhance the leadership, teamwork, and problem-solving abilities of high school students in Ngawi Regency through experiential learning-based training. Sixty students active in school organizations and student activities participated in the program. The implementation methods included interactive lectures, group discussions, simulations, role-playing, educational games, and reflection sessions. Program success was evaluated using pre- and post-tests, participant observation, and satisfaction surveys. Evaluation results showed that the average participant score rose from 61.25 in the pre-test to 84.50 in the post-test, representing an increase of 23.25 points (37.96%). Furthermore, 92.5% of participants found the training material relevant to their needs, and 90.0% reported increased self-confidence in leadership and teamwork. These findings indicate that experiential learning-based training is effective in strengthening students' managerial soft skills, particularly in the areas of leadership, teamwork, and problem-solving.